Tindak Pidana Korupsi dalam Perundang-Undangan di Indonesia - Nganro, Andi Samsan (Fakultas Syariah IAIN Purwokerto, 2010)
The changing of ‘UU’ is intended to guarentee the law, to avoid the different law interpretation and to give protection to the economic and social right. The latets, ‘UU’ no. 20 th. 2001 which is known as the changing of UU no. 31 th. 1999 is about corruption demolishing.